Pragmatystyczne napięcie w amerykańskiej poezji modernistycznej: przypadek Willliamsa - Bartczak, Kacper (Poznańskie Studia Polonistyczne. Seria Literacka, 2014)
The author of the article focuses on the selected short lyrics by William Carlos Williams and simultaneously draws readers attention the tension, existing in the American modernist poetry, between a modernist postulate of the autonomy of an aesthetic object and the pursuit—resulting from the tradition of American pragmatism—to treat this object as an intelligent commentary to customary activities in the environment of human communities. The author’s point of departure is the thesis by Marjorie Perloff. It claims that for modernist writing absolutely “pivotal” is the separation of the realities of the work from the event taking place in real life. Next, he demonstrates why this division cannot be maintained by such poets as Williams and Stevens. This inability is the result of a complex, non-European, pragmatistic admixture feeding the poetics of both poets. The main focus in the article, however, is placed on Williams.